Persepsi, Sikap dan Partisipasi Keluarga Pasien/Pengunjung dalam Menciptakan Kebersihan Lingkungan Rumah Sakit di Kabupaten Manokwari Provinsi Papua Barat - Jumriah; Ihwan Tjolli; Eko Agus Martanto (Program Pascasarjana Universitas Papua, 2021)
This study aims to determine the perceptions, attitudes and expectations of the patient /visitor's family in creating a clean hospital environment and to analyze the factors that influence the participation of the patient's or visitor's family in creating a clean hospital environment. The method used in this research is descriptive method with a quantitative approach. The number of samples taken was 19 samples at each hospital, so the total sample of the study was 38 samples. Data collection was done by means of interviews, observation, and documentation. The results showed that most of the visitors' perceptions of the hospital stated that: (1) hygiene problems are things that must be prioritized and are still being improved, (2) the attitude of the visitors is that most of them agree and support all forms of efforts carried out in the context of hygiene management. hospital environment, (c) the level of visitor participation is mostly in the high category related to the cleanliness of the hospital environment. (4) The results of multiple linear regression analysis show that the variables of formal education, counseling, age and length of visit together have an effect on the level of participation in the cleanliness of the hospital environment. The results of the partial relationship test show that formal education and extension variables have a significant effect on the level of participation. The variables of age and length of visit did not affect the level of participation in the cleanliness of the hospital environment.